Retrospective Assessment of a Serum Proteomic Test in a Phase III Study Comparing Erlotinib plus Placebo with Erlotinib plus Tivantinib (MARQUEE) in Previously Treated Patients with Advanced Non‐Small Cell Lung Cancer. (23rd August 2018) - Buttigliero, Consuelo; Shepherd, Frances A.; Barlesi, Fabrice; Schwartz, Brian; Orlov, Sergey; Favaretto, Adolfo G.; Santoro, Armando; Hirsh, Vera; Ramlau, Rodryg; Blackler, Adele R.; Roder, Joanna; Spigel, David; et al.
Abstract: Background: The VeriStrat test provides accurate predictions of outcomes in all lines of therapy for patients with non‐small cell lung cancer (NSCLC). We investigated the predictive and prognostic role of VeriStrat in patients enrolled on the MARQUEE phase III trial of tivantinib plus erlotinib (T+E) versus placebo plus erlotinib (P+E) in previously treated patients with advanced NSCLC. Methods: Pretreatment plasma samples were available for 996 patients and were analyzed by matrix‐assisted laser desorption/ionization‐time of flight mass spectrometry to generate VeriStrat labels (good, VS‐G, or poor, VS‐P). Results: Overall, no significant benefit in overall survival (OS) and progression‐free survival (PFS) were observed for the addition of tivantinib to erlotinib. Regardless of treatment arm, patients who were classified as VS‐G had significantly longer PFS (3.8 mo for T+E arm, 2.0 mo for P+E arm) and OS (11.6 mo for T+E, 10.2 mo for P+E arm) than patients classified as VS‐P (PFS: 1.9 mo for both arms, hazard ratio [HR], 0.584; 95% confidence interval [CI], 0.468–0.733; p < .0001 for T+E, HR, 0.686; 95% CI, 0.546–0.870; p = .0015 for P+E; OS: 4.0 mo for both arms, HR, 0.333; 95% CI, 0.264–0.422; p < .0001 for T+E; HR, 0.449; 95% CI, 0.353–0.576; p < .0001 for P+E). The VS‐G population had higher OS than the VS‐P population within Eastern Cooperative Oncology Group (ECOG) performance score (PS) categories. VS‐G patients on the T+E arm had longer PFS, but not OS, than VS‐G patients on the P+E arm ( p = .0108). Among EGFR mutation‐positive patients, those with VS‐G status had a median OS more than twice that of any other group (OS: 31.6 mo for T+E and 22.8 mo for P+E), whereas VS‐P patients had similar survival rates as VS‐G, EGFR‐wild type patients (OS: 13.7 mo for T+E and 6.5 mo for P+E). Conclusion: In these analyses, VeriStrat showed a prognostic role within EGOC PS categories and regardless of treatment arm and EGFR status, suggesting that VeriStrat could be used to identify EGFR mutation‐positive patients who will have a poor response to EGFR tyrosine kinase inhibitors. Abstract : The VeriStrat test is a multivariate, mass spectrometry‐based test that measures components of the circulating proteome in the serum of patients with non‐small cell lung cancer. This article reports the results of a retrospective investigation of VeriStrat analyses of pre‐treatment serum samples available from an earlier trial.